Agri and Food Startup Ecosystem in India - Kondapi, Srinivas (Indian Farming, 2020)
Government of India through different policies and schemes like National Intellectual Property Rights (IPR) policy, Make in India, Skill India, Start Up India, Smart Cities, Digital India policies trying to build a strong ecosystem for nurturing innovations and Start-ups/ entrepreneurship in the country. The country predominantly is agrarian as its majority workforce is engaged in it. This sector has a huge potential for promoting innovations as it has rich resources of traditional indigenous knowledge, biodiversity and human capital. The country has gradually started shifting form ‘a producer-driven to demand driven and market-led’ agricultural research and development (R&D) system. ICAR had established 24 Agri-business Incubation (ABI) Centers to nurture early stage innovative startups and entrepreneurs. Ministry of Agriculture’s Rural ABI programme is also gaining momentum. In 2018 agri-tech startups raised around 65.6 million, and food sector startups around 516. The experience of two cases, indicates that the food and agriculture sector has been thronged by the streams of educated youth, fired by the ideas, passion and innovations. These entrepreneurs and start-ups are providing missing links in the agri-value chain and delivering efficient products, technologies and services to the farmers on one hand and the consumers on the other hand. Through two cases it can be inferred that there are better opportunities for nurturing and building innovative enabling platforms for agri-business and agri-entrepreneurship in the country.